A Review of the Myanmar National Community Driven Development Project in Conflict-Affected Contexts - Zurstrassen, Matthew (World Bank, Washington, DC, 2020)
The National Community Driven Development Project (NCDDP) is one of Myanmar’s largest development programs. Since it started in 2013, NCDDP has supported over 21,000 basic infrastructure and services sub-projects in 12,000 villages covering 63 townships, approximately one-fifth of the country. The project is implemented by the Department of Rural Development (DRD) with support from the World Bank and the Governments of Italy and the United Kingdom. This report reviews implementation of NCDDP in townships affected by conflict. It is estimated that a third of townships across Myanmar are affected by conflict. Given NCDDP operates in rural areas across the country a similar proportion of the townships where NCDDP now operates can be defined as conflict-affected.2 The report: examines overall project performance in conflict-affected townships; looks at the effectiveness of specific adaptations to the project that have been introduced to support implementation in townships affected by conflict; and examines the influence the project has had on the broader context in conflict-affected townships. The aim of the report is to inform on-going NCDDP operations and adaptations for operations in conflict-affected townships. The report also aims to inform broader programs, both from the Government of Myanmar and the World Bank, by providing lessons on implementing in conflict-affected areas.